INFORMATION COMMERCIALIZATION IN VIEW OF INFORMATION ETHICS - Anna Waligórska-Kotfas (Taikomieji tyrimai studijose ir praktikoje, 2019)
The information and communication technology revolution has implied socio-economical changes and has led to information commercialization. As a result infobrokering services, professional services to provide information, have emerged. Therefore, the reflection on how to acquire, retrieve, and distribute information in the morally right manner in the information revolution era is crucial. Information ethics can be seen in micro and macro perspective, and an infobroker might be an active constructor of the info-world, improving its nature and shaping its development. However, the codes of ethics and the codes of good practice are fundamental to assist and support infobrokers.